2015
DOI: 10.1128/aac.01477-15
|View full text |Cite
|
Sign up to set email alerts
|

Cefepime Therapy for Monomicrobial Enterobacter cloacae Bacteremia: Unfavorable Outcomes in Patients Infected by Cefepime-Susceptible Dose-Dependent Isolates

Abstract: A new category of cefepime susceptibility, susceptible dose dependent (SDD), for Enterobacteriaceae, has been suggested to maximize its clinical use. However, clinical evidence supporting such a therapeutic strategy is limited. A retrospective study of 305 adults with monomicrobial Enterobacter cloacae bacteremia at a medical center from 2008 to 2012 was conducted. The patients definitively treated with in vitro active cefepime (cases) were compared with those treated with a carbapenem (controls) to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 18 publications
3
41
2
Order By: Relevance
“…This finding is in line with the recent results by Lee et al [13]. They reported that 63.6% of 217 E. cloacae blood isolates were cefepime-susceptible and 19.8% were cefepime-SDD [13]. Hence, laboratories that choose to implement the new CLSI criteria for Enterobacteriaceae should clearly inform treating physicians regarding the SDD category, so that they can be alert to the possible need for higher doses of cefepime in treating infections caused by these organisms.…”
supporting
confidence: 94%
See 2 more Smart Citations
“…This finding is in line with the recent results by Lee et al [13]. They reported that 63.6% of 217 E. cloacae blood isolates were cefepime-susceptible and 19.8% were cefepime-SDD [13]. Hence, laboratories that choose to implement the new CLSI criteria for Enterobacteriaceae should clearly inform treating physicians regarding the SDD category, so that they can be alert to the possible need for higher doses of cefepime in treating infections caused by these organisms.…”
supporting
confidence: 94%
“…In contrast, we found that applying the new cefepime CLSI criteria led to a substantial change in the susceptibility rates of cefepime against Enterobacteriaceae producing AmpC β-lactamase. This finding is in line with the recent results by Lee et al [13]. They reported that 63.6% of 217 E. cloacae blood isolates were cefepime-susceptible and 19.8% were cefepime-SDD [13].…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Clinical data on outcomes for patients with infections caused by ESBL-E who were treated with active cephalosporins versus other options are limited and sometimes contradictory (68,(74)(75)(76)(77)(78)(79). Goethaert et al found similar mortality rates for 21 and 23 patients with BSI due to TEM-23-producing Enterobacter aerogenes who were treated empirically with cefepime (2 g every 8 h) and carbapenems, respectively (74).…”
Section: Oxyiminocephalosporins (Cefotaxime Ceftriaxone Ceftazidimementioning
confidence: 99%
“…Cefepime, a 4 th -generation cephalosporin, may have a role in the treatment of AmpC-E infections, as it has relative stability against AmpC β-lactamases compared to other cephalosporins. Two observational studies of AmpC-E infections showed no differences in outcomes between patients treated with either carbapenems or cefepime [28,29]. The role of PTZ in the treatment of serious AmpC-E infections is not well established.…”
Section: Ampc β-Lactamase-producing Enterobacteriaceae (Ampc-e)mentioning
confidence: 99%